Hearing loss in lateral medullary syndrome. Issue 6 (12th August 2016) - Sato, Kenichiro; Hida, Ayumi; Omori, Aki; Arai, Noritoshi; Takeuchi, Sousuke
Abstract: We report a case of lateral medullary syndrome with hemiparesis and hearing loss. A 69‐year‐old man was diagnosed with right‐sided lateral medullary syndrome and cerebellar vermis infarction with ipsilateral hemiparesis as a result of an upper cervical lesion. On the seventh hospital day, ipsilateral hearing loss suddenly emerged. The results of auditory and vestibular tests, including auditory brainstem responses, suggested a possible lesion in the vestibulocochlear nerve. Hearing loss could be attributed to a non‐anterior inferior cerebellar artery, vertebral artery and/or posterior inferior cerebellar artery infarction. The possibility of comorbidity of hearing loss with lateral medullary syndrome in this case suggests the possible usefulness of further intensive antithrombotic therapy in cases of lateral medullary syndrome with uncommon presentations.